Defect investigation and replacement implementation of bearings for long-span continuous box girder bridges under operating high-speed railway networks: a case study. Issue 5 (4th May 2022) - Ma, Fengbo; Li, Huile; Hou, Shitong; Kang, Xuecheng; Wu, Gang
Abstract: Bridge bearings easily suffer damage when exposed to various loading and environmental changes during their lifetime. This effect can have a considerable impact on the bridge service performance, and bearing replacement should be performed if damage occurs. Compared with highway bridges, bearing replacement for long-span bridges under operating high-speed railways (HSRs) is more challenging due to the higher safety requirements for the operation of trains, the larger jacking reaction forces for single piers and the complex bearing structures. In this paper, the defects of bearings in five larger-scale HSR bridges are investigated through field detection, followed by a bridge jacking scheme that includes a temporary support with a continuous height adjustment, a large bearing capacity and good stability. Finally, a replacement method using the invented temporary support and a developed reverse disassembly or assembly technology as well as safety monitoring is proposed and implemented on the bridge. The results show that most defects are caused by the problems remaining from bearings installation, which are aggravated during a long service period, and that the proposed jacking scheme is feasible, which sheds light on the maintenance and replacement of bearings for long-span bridges under operating HSR networks.